2018
DOI: 10.1007/s10479-018-3051-4
|View full text |Cite
|
Sign up to set email alerts
|

Manage risk of sustainable product–service systems: a case-based operations research approach

Abstract: Sustainable product-service systems (SusPSSs) offer an innovation-driven approach to production based on providing results or functions with minimal material use and emissions. Networks of SusPSSs partners are central to the decision-making of sustainability policies. Evaluations and assessments of networkoriented risks sources are therefore crucial to informing an industrial firm's reorientation towards SusPSS.Traditionally, these risks beleaguer production and continue to grow in significance with complex pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 78 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…However, Van Gils et al (2018, 2019) argue that genetic algorithms provide biased solution to the problems due to infinite nature of problems. Wang et al (2018a, 2018b) elaborate agent-based system as the process by which a bigger problem is dissected into a smaller one, which can be solved alternatively. It increases the problem-solving capabilities of artificially designed systems enabling wider coverage.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, Van Gils et al (2018, 2019) argue that genetic algorithms provide biased solution to the problems due to infinite nature of problems. Wang et al (2018a, 2018b) elaborate agent-based system as the process by which a bigger problem is dissected into a smaller one, which can be solved alternatively. It increases the problem-solving capabilities of artificially designed systems enabling wider coverage.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Great complexities can be given for the coordination and control work when multiple players hold dispersed geographic locations or misaligned interest goals (Noori and Lee, 2007). Similarly, Wang et al (2018) also suggested that system-level controls have to face greater uncertainties. For instance, as the negative effect of information exchange among actors, knowledge leakage may be incurred, leading to the loss of control over their partners (Lockett et al, 2011).…”
Section: Possible Negative Outcomesmentioning
confidence: 99%
“…(Hedvall et al, 2019) "All these companies extend the traditional, vertically-integrated, supplier-customer relationship with service networks thus enabling them to provide services, that play a key role in the offer of solutions." (Gebauer et al, 2013) Sus PSS Sustainable product-service systems (Sus PSSs) offer an innovation-driven approach to production based on providing results or functions with minimal material use and emissions (Wang et al, 2018) "The co-development of a solution based on a partnership between private and public organizations resulted in an innovative and sustainable solution that would not have been possible without all the parties involved. "In eco-efficient PSSs, a key element is the network of stakeholders that produce and deliver the solution to customers."…”
Section: Limitationsmentioning
confidence: 99%
“…In the context of green or sustainable supply chain management, Touboulic et al (2014) investigate an imbalanced supply chain relationship for sustainability, and their study illustrates the influences of power on how supply chain members manage their relationships and its effect on organisational responses to sustainability implementation. Wang et al (2018) present a novel technique to evaluate and assess the network-oriented risks in sustainable productservice systems (SusPSSs) to minimise the material use and emissions. Considering the supply chain power relationship, Chen et al (2017) design a two-part tariff contract is to coordinate the supply chain with a goal of optimising the economic and environmental performance.…”
Section: Research Background and Related Literaturementioning
confidence: 99%
“…Furthermore, different industry sectors (e.g., steel, construction, telecommunication, retailing, and many others) have their distinctive supply chain power relationships, investment efficiencies and customers' carbon emissions sensitivity in carbon emissions reduction. Through considering the effects of supply chain power structures and green technology investment efficiencies on the optimal carbon emissions tax design, we also contribute to the "power (or supply chain leadership)" literature (Touboulic et al 2014;Du et al 2015;Chen and Hao 2015;Park et al 2015;Chen et al 2017;Wang et al 2018) and the green technology investment literature (Krass et al 2013;Drake et al 2015;Bi et al 2017;Han et al 2017;Li et al 2019) in the context of the sustainable supply chain management. Practically, we have derived the optimal solutions under the carbon emissions tax, helping firms make optimal operational and technology investment decisions to improve their economic and environmental performances.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%